2021
DOI: 10.1111/ane.13404
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 presentations and outcome in patients with epilepsy

Abstract: Objective To determine whether patients with epilepsy (PWE) are particularly over‐represented in a very large cohort of patients with COVID‐19. We also investigated whether COVID‐19 is associated with a different clinical picture or a more severe course of illness in PWE (compared with others). Methods All consecutive patients who referred to and admitted at healthcare facilities anywhere in Fars province (located in the south of Iran with a population of 4,851,000 peop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 14 publications
2
38
0
2
Order By: Relevance
“…In a recent study, we observed that patients with epilepsy were not susceptible to contracting COVID-19 more than that in other individuals. Furthermore, COVID-19 in patients with epilepsy was not associated with a poorer prognosis [17]. In the current study, the seizure outcome in patients, who were hospitalized with COVID-19 and seizures, were generally good.…”
Section: Discussionmentioning
confidence: 42%
“…In a recent study, we observed that patients with epilepsy were not susceptible to contracting COVID-19 more than that in other individuals. Furthermore, COVID-19 in patients with epilepsy was not associated with a poorer prognosis [17]. In the current study, the seizure outcome in patients, who were hospitalized with COVID-19 and seizures, were generally good.…”
Section: Discussionmentioning
confidence: 42%
“…An early analysis of COVID-19 admissions showed an association between epilepsy and age with a fatal outcome after contracting COVID-19 [5] . In contrast, larger studies did not find any evidence that a SARS-CoV-2 infection per se leads to a worse outcome in PWE than in the normal population [6] . Nevertheless, negative impact of COVID-19 pandemic on PWE in terms of health and health care is well described [7] .…”
Section: Introductionmentioning
confidence: 71%
“…Eleven article were excluded after the assessment because the outcomes outlined in seven of the articles did not meet the criteria of the present study, three articles had no information on a control group, and one article was not published in English. Thus, 13 studies [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , which included a total of 67,131 patients with COVID-19, were included in the analysis ( Figure 1 ). Of the 13 studies, eight were retrospective cohort studies, three were case-control studies, and two were case-series studies.…”
Section: Resultsmentioning
confidence: 99%